A diode-based two-wire solution for temperature-compensated piezoresistive pressure sensors. - Melvas, P.
A novel two-wire solution for ultraminiaturized temperature-compensated piezoresistive pressure sensors is presented. The technique makes it possible to measure both pressure and temperature separately by using bias-controlled diodes as switches between the pressure and temperature sensing elements. The p-n junction diodes are forward-biased or reverse-biased depending on the polarization of the voltage supply. The new diode-based two-wire technique was evaluated using a surface micromachined pressure sensor where the pressure-sensing element consists of a piezoresistor on an (80×40×1 μm) double end supported force- transducing beam. The beam is located beneath a (100×100×2 μm) square polysilicon diaphragm having its ends attached to the diaphragm and to the cavity edge. The thermal compensation piezoresistor is also located in the cavity on a (100×40×1 μm) beam. Both ends of this beam are attached to the cavity edge and are therefore pressure-insensitive. The new detection solution enables a reduction of conducting leads from three to two in combination with high pressure sensitivity (0.7 μV/V/mmHg) and environmental isolation compared to a commercialized traditional piezoresistive pressure sensor. Its simplicity and the potential for size reduction due to fewer bonding pads and conducting wires make it ideal for applications such as disposable blood pressure sensors where cost and size are critical parameters.
Keywords: Si; Bias-controlled diodes switches; Diode-based two-wire technique; Disposable blood pressure sensors; Double end supported beam; Force-transducing beam; P-n junction diodes; Piezoresistive pressure sensors; Polysilicon diaphragm; Pressure sensing element; Surface micromachined pressure sensor; Temperature sensing element; Temperature-compensated pressure sensors; Thermal compensation piezoresistor; Ultraminiaturized pressure sensors